The Expression of Cyclin D1, VEGF, EZH2, and H3K27me3 in Atypical Teratoid/Rhabdoid Tumors of the CNS: A Possible Role in Targeted Therapy. Issue 10 (November 2016) - Kakkar, Aanchal; Biswas, Ahitagni; Goyal, Nishant; Suri, Vaishali; Sharma, Mehar C.; Gupta, Deepak; Julka, Pramod K.; Sarkar, Chitra
Abstract : Atypical teratoid/rhabdoid tumor (AT/RT) is an uncommon malignancy with a dismal outcome, which responds poorly to multimodality therapies. Animal studies have revealed Cyclin D1 as a possible therapeutic target. The addition of vascular endothelial growth factor (VEGF) inhibitors to chemotherapeutic regimens has shown promising results in pediatric central nervous system tumors. Enhancer of Zeste homolog 2 (EZH2) overexpression has been implicated in various cancers, including medulloblastomas. H3K27me3 is a new marker for pediatric high-grade gliomas. However, their role in AT/RT has not been evaluated sufficiently. We retrieved cases of AT/RT, and reviewed their clinical data and histopathologic features. Immunohistochemistry for Cyclin D1, VEGF, EZH2, and H3K27me3 was performed. Follow-up was noted when available. Fourteen cases of AT/RT were identified (mean age, 3.4 y; range, 10 mo to 8 y). Cyclin D1 immunopositivity was noted in all cases [labeling index (LI): 5% to 98%; mean, 41.3%]. VEGF positivity was seen in 83.3% of the cases. All cases showed EZH2 overexpression (mean LI, 74.3%; range, 32% to 96%). Reduction of H3K27me3 expression was noted in 63% of the cases, with no correlation with EZH2 LI. Two patients died of postoperative complications. Of the rest, follow-up was available for 7 (range, 7 to 120 wk): 1 achieved clinical remission, whereas 6 developed progressive disease, including 3 deaths. Varying degrees of immunoreactivity to Cyclin D1, VEGF, and EZH2 were noted in the majority of the AT/RTs, and detection of these markers may be of value in the development of novel therapeutic agents and in determining which patients can benefit from them. AT/RTs show reduction in H3K27me3 expression, independent of EZH2 expression, indicating that their interaction requires further evaluation.